2011
DOI: 10.2399/ana.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting anatomical landmarks of cadaveric nerve-sparing radical prostatectomy in accordance to Terminologia Anatomica

Abstract: Objectives: Because of the developing and standardizing urology resident education, we aimed to show important anatomical landmarks of nerve-sparing radical prostatectomy in a cadaveric dissection. Methods:The steps of the dissection were; 1) Incision of pelvic fascia, 2) Dissection of the puboprostatic complex, 3) Dissection of the urethral sphincteric complex and apical dissection of the prostate and urethra, 4) Dissection of the posterior part of the prostate, 5) Preservation of the neurovascular bundle (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nielsen et al [ 16 ] reported excellent oncological results and improved postoperative sexual function after this technique. I suggest that working collaboratively with a clinical anatomist is crucial to update the anatomical terminology of the prostate, which contiguous structures are clinically useful, and the surgical procedure [ 56 ].…”
Section: Fsrp: Novel Anatomical Identificationmentioning
confidence: 99%
“…Nielsen et al [ 16 ] reported excellent oncological results and improved postoperative sexual function after this technique. I suggest that working collaboratively with a clinical anatomist is crucial to update the anatomical terminology of the prostate, which contiguous structures are clinically useful, and the surgical procedure [ 56 ].…”
Section: Fsrp: Novel Anatomical Identificationmentioning
confidence: 99%